How social entrepreneurship relates to graduate employability?: A conceptual framework - Abdul Malek, A Tambi; Nik Fazlin Hiryati, Nik Jaafar (2016)
There are a plethora studies exploring ways of improving graduate employability that involved various stakeholders to the issues, yet ignoring the other promising perspective that might be very helpful. Supplementary study on how social entrepreneurship may contribute to the issue would be worth enough to be explored otherwise, this inadequate studymight hinder the aspiration to achieve passable percentage of employability level set. Only those graduates with appropriate skill and ability such as, among others; critical thinking, communication skills, and language proficiency, will be able to compete curren in today’s challenging workforce market. Hence modelling the social entrepreneurship to overcome the graduate employability issue is very important. Building on the previous researches, this paper may offer a deeper conception about the relationship between graduate employability and social entrepreneurship. Particularly, a conceptual model is developed linking different components of social entrepreneurship and provide insight how it may contribute to employability level among graduates.